Determination of Heavy Metals in Locally Available Chocolates in Lahore Region - Muhammad Amjad; Shabbir Hussain; Zia Ur Rehman Baloch; Aoun Raza (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Heavy metal toxicity can either be acute or chronic effects. Long-term exposure of the body to heavy metal can progressively lead to muscular, physical and neurological degenerative process. In this research, a total of 30 representative chocolate samples were collected from local shops and markets in Lahore. All the samples were analysed to assess the levels of Lead (Pb), Nickel (Ni), Chromium (Cr) and Cadmium (Cd) by using Atomic Absorption Spectrophotometer in Pakistan Council of Scientific and Industrial Research (PCSIR), Lahore. It was observed that the majority of chocolate samples contain heavy metals levels higher than the permissible limits as recommended by Punjab Food Rules (PFR) 2011. The levels of Pb ranged between 0.375 and 3.4 mg/kg with 90% samples having concentrations exceeding PFR allowable limit (0.5 mg/kg). Whereas, Ni concentrations varied from 0.005 to 0.28 mg/kg and 80% samples were above the PFR limit (0.025 mg/kg). Further, Cr levels analysed between 0.005 to 0.28 mg/kg and 53% samples had Cr concentrations higher than PFR limit (0.02 mg/kg). Similarly, Cd levels were observed between 0.50-3.25 mg/kg with 53% samples having Cd concentrations exceeding the PFR limit (1.0 mg/kg). Investigation indicates that the quality of available chocolates is not recommendable for eating because of the higher concentrations of toxic heavy metals.